2016
DOI: 10.3329/bjm.v31i1.28463
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Biofilm Formation Ability of Clinical Isolates of Salmonella enterica Serovars Typhi and Paratyphi

Abstract: In the present study the ability of clinical isolates of Salmonella enterica serovars Typhi (n = 30) and Paratyphi A (n = 11) to form biofilm on abiotic surface was investigated. All isolates were found capable of biofilm formation in a microtitre plate assay. Upon optimization of biofilm formation by the test isolates, Adherence test medium (ATM) was found to be the best medium for biofilm formation by both S. enterica serovars Typhi and Paratyphi. Growth was optimized by incubation at 37°C in an orbital shak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The current study findings of SAL 1 and SAL 3 showing different biofilm-forming abilities may vary their pathotypes. Current study findings of the optimum biofilm-forming ability of Salmonella isolate (Salmonella 3) at 48hr also agreed with several previous findings [30,31,32]. Among those findings, Shatila et al [32] has observed more prominent curli and cellulose production at 48hr.…”
Section: According To Fernández Et Al [24] Clinicalsupporting
confidence: 91%
“…The current study findings of SAL 1 and SAL 3 showing different biofilm-forming abilities may vary their pathotypes. Current study findings of the optimum biofilm-forming ability of Salmonella isolate (Salmonella 3) at 48hr also agreed with several previous findings [30,31,32]. Among those findings, Shatila et al [32] has observed more prominent curli and cellulose production at 48hr.…”
Section: According To Fernández Et Al [24] Clinicalsupporting
confidence: 91%